From Novorossiisk to Alexandria: British Involvement in the Evacuation of White Russian Refugees, 1920. (3rd July 2019) - Konn-Roberts, Tania
ABSTRACT: Events during Russia's Civil War (1918–1920) produced a serious refugee crisis focused on the port of Novorossiisk in south Russia towards the end of 1919 and the opening months of 1920. Lloyd George's Coalition Government was persuaded to support a rescue mission of selected refugees with most to fear from a Bolshevik victory. The decision was taken against Admiralty advice and against Treasury unwillingness to meet expected high resettlement costs. Thousands of White Russians were rescued and, without wishing or planning the end, the British Government found itself saddled with distracting refugee responsibilities in the politically unstable Protectorate of Egypt.